Optimalisasi Produksi untuk Meningkatkan Profitabilitas Usahatani Kangkung dan Bayam di Kecamatan Merawang Kabupaten Bangka - Khasanah, Nur; Muharani, Laily; Wiyandi, Igus; Prihardi, M Galvin (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
Horticulture is one of the agricultural sub-sectors that contributes to economic development in Indonesia. This is because horticulture is a subsector in agriculture that has the potential to be developed, because it has an important role in contributing to farmers' income and trade. Kale and spinach are examples of horticultural vegetables that have this potential, because both vegetables are types of vegetables that are always in demand by the community for consumption. This potential can provide benefits for producers, consumers and society. This study aims to: (a) Calculate the optimal amount of green vegetable production (b) Calculate the maximum income that can be received by green vegetable farmers. This research was conducted in Merawang District, Bangka Regency. The analysis method used was Linear Programming analysis. Linear Programming is an operations research technique by solving optimization problems using linear equations and inequalities. The results of the analysis resulted in the maximum income solution value of kale and spinach farming in Merawang District, which is a maximum of Rp 17,355,000 per land area of 0.34 hectares or Rp 51,044,117 per hectare. Based on the results of linear program analysis, the optimal amount of products that farmers can produce for kale products is 3.39 tons per land area of 0.20 hectares or 16.95 tons per hectare, and for spinach products is 1.95 tons per land area of 0.14 hectares or 13.9 tons per hectare.